2012
DOI: 10.1159/000343839
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Treatment Strategies for Patients with Advanced Hepatocellular Carcinoma: Role of mTOR Inhibition

Abstract: Hepatocellular carcinoma (HCC) is a common cancer that has the third highest cancer-related mortality rate worldwide. Although potentially curable by transplantation if detected early, the majority of cases are diagnosed at an advanced stage of disease for which limited treatment options are available. The only proven systemic therapy for advanced HCC is sorafenib, a multi-kinase inhibitor that has demonstrated modest efficacy and reasonable tolerability in patients with advanced HCC. Five years after the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 49 publications
(76 reference statements)
0
41
0
1
Order By: Relevance
“…It was recently demonstrated that mTOR inhibitors have anti-tumor effects (Bijnsdorp et al, 2011;Finn., 2012;Migliardi et al, 2012). However, our study failed to determine the relationship between the expression of P-S6 (S235/236), DEPTOR and overall survival in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that mTOR inhibitors have anti-tumor effects (Bijnsdorp et al, 2011;Finn., 2012;Migliardi et al, 2012). However, our study failed to determine the relationship between the expression of P-S6 (S235/236), DEPTOR and overall survival in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR signaling plays a role in tumor angiogenesis and proliferation that is important in carcinogenesis of HCC [70] . In LT for HCC, sirolimus based immunosuppression was reported to be associated with lower tumor recurrence rate, longer recurrencefree survival and overall survival, and lower recurrencerelated mortality compared with CNIs [71] .…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…Everolimus, the only oral, mTOR inhibitor has established efficacy in advanced renal cell carcinoma, advanced neuroendocrine tumours and hormone receptor positive/human epidermal growth factor receptor-2 negative advanced breast cancer [3]. mTOR inhibition with everolimus, both in vitro (Human HCC cell lines) and in vivo (murine xenograft model) was documented to reduce tumor growth and increase survival.…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus is the orally active mTOR inhibitor approved in anticancer applications and could be a potential option for advanced HCC treatment [3,5]. Here we report a case of successful cessation of advanced, unresectable HCC progression with the continued therapy of everolimus.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation